Pengaruh Model Pembelajaran Round Club Terhadap Keterampilan Berbicara Siswa Kelas IV SDN Inpres 162 Kampung Beru Kabupaten Takalar - Rachmatiah Rachmatiah; Andi Sukri Syamsuri; Abdul Rajab (STIKes Ibnu Sina Ajibarang, 2024)
The main problem of this research is whether there is an effect of implementing the Round Club model on the speaking skills of students at SDN Inpres 162 Kampung Beru, Takalar Regency. This research aims to describe the influence of the Round Club learning model on the speaking skills of class IV students at SDN Inpres 162 Kampung Beru, Takalar Regency. This type of research is pre-experimental research in the form of Pretest Posttest Design, namely an experiment which in its implementation only involves one class as an experimental class without a comparison class (control class) which aims to determine the effect of the Round Club Model on the Speaking Skills of Class IV Students at SDN Inpres 162 Beru Village, Takalar Regency. The subjects of this research were 20 class IV students of SDN Inpres 162 Kampung Beru, Takalar Regency. The results of the research show that the learning outcomes of class IV students before the implementation of the Round Club learning model which was completed individually out of 20 students, only 7 students or 35% met the Minimum Completeness Criteria (KKM) or were in the low category. Classically it has not been fulfilled because the average pretest score is 66.8%. Meanwhile, when implementing the Round Club learning model which was completed individually, out of 20 students, 18 students or 90% had fulfilled the KKM and classically had been met, namely the average posttest score obtained was 82.5%, which was categorized as high. This proves that there is an influence of the Round Club Learning Model on Speaking Skills in Class IV Students of SDN Inpres 162 Kampung Beru, Takalar Regency.